2016
DOI: 10.4172/2155-6199.1000366
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Biological Approach for the Effluent Treatment of Paper Boards Industry - An Economic Perspective

Abstract: The environmental problems of paper board industry are not limited by the high water consumption, generate wastewaters and solid wastes. This paper presents the paper board industry effluent treatment plant components performance and physio-chemical characteristics of wastewater and sludge. In ETP operation most important factors is effluent characterization, flow rate, aeration tank dissolved oxygen (DO) level, mixed liquid suspended solids (MLSS), food to micro-organism ratio (F/M), sludge volume and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Since the pH is not acidic, this would reduce the heavy metal absorption ability of the sludge and hence reduce the possible toxicity [16]. According to Rajkumar [20], activated sludge can only be suitably applied to the biological treatment if the pH value is near neutral at approximately 6.5-7.5. Th e EC of the sludge samples ranged from 758.7 ± 8.08 µS/ cm to 1735.7 ± 109.7 µS/ cm.…”
Section: A Ph and Electrical Conductivity (Ec)mentioning
confidence: 99%
“…Since the pH is not acidic, this would reduce the heavy metal absorption ability of the sludge and hence reduce the possible toxicity [16]. According to Rajkumar [20], activated sludge can only be suitably applied to the biological treatment if the pH value is near neutral at approximately 6.5-7.5. Th e EC of the sludge samples ranged from 758.7 ± 8.08 µS/ cm to 1735.7 ± 109.7 µS/ cm.…”
Section: A Ph and Electrical Conductivity (Ec)mentioning
confidence: 99%
“…Level of Treatment (2017) conducted a study of decentralized sewage treatment which stated DO at receiving point is lower than detection limit and greater than 2 mg/l at outlet [6]. Also a Bhaarat et al conducted a study on wastewater of pharmaceutical industry which resulted in 1.4 mg/l DO at receiving point and 4.5 mg/l at outlet [7].…”
Section: Purpose/usementioning
confidence: 99%
“…Patil et al (2018) performed a study on design of sewage treatment plant units which stated BOD of 189.78 mg/l at receiving point and 30-150 mg/l at outlet [9]. The outcome of study conducted by Bhagwatkar et al (2017) on decentralized sewage treatment reported 100-200 mg/l at receiving point and less than 5 mg/l at outlet [6]. Dahamsheh and Wedyan (2017) performed a study on interpretation of performance of sewage treatment plant which recorded BOD of 335.7 mg/l at receiving point and 15.5 mg/l at outlet [10].…”
Section: Purpose/usementioning
confidence: 99%
See 1 more Smart Citation
“…The paper industries hold an important place in Spanish economy, as Spain is one of the European leaders in paper recycling, with 84% of the raw materials used by the paper industry containing recovered paper [ 2 ]. However, we cannot forget that water is, also, an essential raw material for manufacturing paper and paperboard, and effluent treatment is a critical part of the process [ 3 ]. In order to minimize the amount of freshwater used and the volume of effluent discharged, the European Commission has described the best available techniques to be adopted by the P & P industry [ 4 ].…”
Section: Introductionmentioning
confidence: 99%